Culture of engagement: Students as change agents before, during and after an examination-focused partnership - Fransén, Lina; Hellgren, Victor; Mortensen, Magnus; Olsson, Susanna; Proos Vedin, Nathalie; Elmgren, Maja; Lundberg, Marcus; Kotronia, Antonia (International Journal for Students as Partners, 2024)
Students can influence their education through evaluations and as representatives in university decision-making bodies. A way to give them more power is through participation in course development as equal partners. In this study, the relationship between the outcome of a student-teacher partnership and a culture of student influence and engagement is explored. This is done through specifically targeting examination, an area where formal power rests far away from the actual partnership. The partnership outcome was evaluated through post-project surveys and group interviews, together with post-course evaluations. The students in the project, most of them with significant experience as student representatives, emphasized their ability to make meaningful change. At the same time, the students taking the revised course appreciated the implemented changes. A culture of engagement positively affected the outcome of the partnership, while the partnership itself strengthened students in their roles as change agents.